Manajemen Zakat Produktif dengan Sistem Dana Bergulir di LAZNAS Nurul Hayat Madiun - Sari, Hesti Tri Indah; Amri, Muhtadin (Institut Agama Islam Negeri Ponorogo, 2023)
This study discusses the implementation of productive zakat that hopefully can improve the welfare of mustahik significantly so that the zakat funds do not stop at one mustahik only. This study aims to analyze the mechanism of productive zakat management with a circulated fund system at LAZNAS Nurul Hayat Madiun, the optimization of the circulated fund system for productive zakat at LAZNAS Nurul Hayat Madiun, and the supporting and inhibiting factors of productive zakat management with circulate fund system at LAZNAS Nurul Hayat Madiun. This research uses a qualitative research method with a descriptive approach. The type of study is field study research. There are three main points from the results of this study. First, productive zakat management with a circulated fund system to improve the welfare of mustahik has been going well. Classification of mustahik, funding, outreach and surveys, coordination, assistance, and supervision of mustahik are all going according to the plans. Second, the optimization of the circulated fund system is going well through the systematization of funds which is carried out in stages, and a program monitoring system which is executed once a month. Third, the supporting factor is the good synergy between parties, while the inhibiting factors are the less optimal role of authorized staff, the planning of fund allocations that need to be evaluated and reconsidered, the lack of direction from the institution's leaders regarding entrepreneurship and the recording of financial reports. Studi ini membahas mengenai implementasi zakat produktif yang diharapkan mampu meningkatkan kesejahteraan mustahik secara signifikan sehingga dana zakat produktif yang ada tidak hanya berhenti pada satu mustahik saja. Tujuan penelitian ini adalah untuk menganalisis mekanisme pengelolaan zakat produktif dengan sistem dana bergulir di LAZNAS Nurul Hayat Madiun, optimalisasi sistem dana bergulir pada zakat produktif di LAZNAS Nurul Hayat Madiun, dan faktor pendukung serta penghambat pengelolaan zakat produktif dengan sistem dana bergulir di LAZNAS Nurul Hayat Madiun. Penelitian ini menggunakan metode penelitian kualitatif dan bersifat deskriptif dengan jenis penelitian studi lapangan. Terdapat tiga hal utama dari hasil penelitian ini. Pertama, manajemen zakat produktif dengan sistem dana bergulir untuk meningkatkan kesejahteraan mustahik telah berjalan baik. Penggolongan mustahik, dana, sosialisas dan survey, koordinasi, pemberian bantuan, dan pengawasan mustahik seluruhnya berjalan sesuai dengan perencanaan. Kedua, optimalisasi sistem dana bergulir berjalan dengan baik melalui sistematisasi dana yang dilakukan secara bertahap dan sistem pengawasan program yang dilakukan sebulan sekali. Ketiga, faktor yang mendukung adalah adanya sinergi antarpihak yang baik, sedangkan faktor-faktor yang menghambat adalah peran staf berwenang yang kurang maksimal, perencaan alokasi dana yang perlu dievaluasi dan dipertimbangkan kembali, kurangnya arahan dari pihak lembaga mengenai kewirausahaan dan pencatatan laporan keuangan.